Tensionless super p-branes in extended superspaces - Uvarov, D.V.; Zheltukhin, A.A. (Вопросы атомной науки и техники, 2007)
Analyzed is the symmetry structure of tensionless super p-branes in N=1 superspace enlarged by commuting antisymmetric tensor coordinates zm1 - mp associated to tensorial central charge generators of N=1 extended superalgebra. Using the conversion method we find the constrained Hamiltonian, classical BRST generator and the generators of global and local symmetries of the p-brane model. Quantum realizations of the BRST generator and symmetry generators of super p-brane action are discussed. Представлений аналіз структури симетрій супер p-бран з нульовим натягом у N=1 суперпросторі, розширеному переставними антисиметричними тензорними координатами zm1 - mp, які відповідають генераторам тензорних центральних зарядів N=1 розширеної супералгебри. З використанням методу конверсії отримано функцію Гамільтона, класичний БРСТ-генератор та генератори глобальних та локальних симетрiй моделей р-бран. Обговорюються квантові реалізації БРСТ-генератора та OSp(1|8)-генераторів. Представлен анализ структуры симметрий супер p-бран с нулевым натяжением в N=1 суперпространстве, расширенном коммутирующими антисимметричными тензорными координатами zm1 - mp, отвечающими генераторам тензорных центральных зарядов N=1 расширенной супералгебры. Используя метод конверсии, получены функция Гамильтона, классический БРСТ-генератор и генераторы глобальных и локальных симметрий моделей р-бран. Обсуждаются квантовые реализации БРСТ-генератора и OSp(1|8)-генераторов.